Synthesis and antifungal activity of 1,5-disubstituted-1,2,3-triazole containing fluconazole analogues - Pore, Vandana S.; Jagtap, Manisha A.; Agalave, Sandip G.; Pandey, Atindra K.; Siddiqi, Mohammad I.; Kumar, Vikash; Shukla, Praveen K. (Medchemcomm, 2012)
Fluconazole based novel mimics containing 1,5-disubstituted 1,2,3-triazoles were synthesized by using Ru catalysed 1,3 dipolar cycloaddition. All the newly synthesized compounds and pure enantiomers were more potent than fluconazole against Candida albicans. Docking of 9A and 9B showed different conformation in the active site of Cyp51 of Candida albicans. The more active compounds 2 and 2A did not exhibit any toxicity up to 3.12 mu g mL(-1) against mammalian cell line L929.

Design and synthesis of new fluconazole analogues - Pore, Vandana S.; Agalave, Sandip G.; Singh, Pratiksha; Shukla, Praveen K.; Kumar, Vikash; Siddiqi, Mohammad I. (Organic & Biomolecular Chemistry, 2015)
We have synthesized new fluconazole analogues containing two different 1,2,3-triazole units in the side chain. The synthesis of new amide analogues using a variety of acids is also described. All the compounds showed very good antifungal activity. A hemolysis study of the most active compounds 6e and 13j showed that both compounds did not cause any hemolysis at the dilutions tested. These compounds did not exhibit any toxicity to L929 cells at MIC and lower concentrations. In the docking study, the overall binding mode of 6e and 13j appeared to be reasonable and provided a good insight into the structural basis of inhibition of Candida albicans Cyp51 by these compounds.

High-level supercapacitive performance of chemically reduced graphene oxide - Jha, Plawan Kumar; Singh, Santosh Kumar; Kumar, Vikash; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Chem, 2017)
Reduction of graphene oxide (GO) is an important process because it holds promise for the production of reduced graphene oxide (rGO) with physicochemical properties similar to those of pristine graphene. In conventional chemical reduction, strong reducing agents, such as sodium borohydride and hydrazine, cannot be recycled. Also, fast reaction kinetics bring an imbalance in the desirable properties of rGO. Here, we present one-pot chemical reduction of GO in aqueous medium by an unconventional mild reducing agent (FeCl2/HCl) where rGOis isolated as the precipitate and the reducing agent is recycled upon simple treatment of the filtrate with HCl. The fabricated all-solid-state supercapacitors of as-synthesized rGO exhibited significantly higher specific capacitance than those obtained with rGO derived from conventional reducing agents. The cycling stability of the all-solid-state supercapacitor (> 80% retention of capacitance beyond 100,000 continued cycles) and its flexibility (> 500 bending cycles) were remarkable. Use of commercially available organic electrolyte further boosted the supercapacitor performance.

In-situ generated Mn3O4-reduced graphene oxide nanocomposite for oxygen reduction reaction and isolated reduced graphene oxide for supercapacitor applications - Jha, Plawan Kumar; Kashyap, Varchaswal; Gupta, Kriti; Kumar, Vikash; Debnath, Anil Krishna; Roy, Debashree; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Carbon, 2019)
We have generated in situ nanocomposite of Mn3O4 and reduced graphene oxide (rGO) upon employing wet-chemical reduction of graphene oxide (GO) by Mn(II) salt as mild-reducing agent for the first time and examined the oxygen reduction reaction (ORR) activity in 0.1 M KOH electrolyte. The half-wave potential (E-1/2) of the nanocomposite catalyst (20% Mn3O4-rGO/C) was found to be around -0.153 V which is only similar to 87 mV negative from the commercially available catalyst (20% Pt/C). Remarkably, after 5000 linear sweep voltammetry cycles the E-1/2 shifted marginally by 20 mV; and the number of electrons transferred during ORR was estimated to be close to 4. Such an efficient electrocatalytic performance of the nanocomposite was primarily attributed to the synergistic interaction between Mn3O4 and rGO. The fabricated all-solid-state supercapacitor of rGO (extracted from the nanocomposite) in aqueous polyvinyl alcohol-sulfuric acid (PVA-H2SO4) gel polymer electrolyte (GPE) showed C-s value of similar to 310 F/g at a current density of 1 A/g along with long durability (10,000 charge-discharge cycles). All-solid-state flexible rGO supercapacitor exhibited high-flexibility and excellent durability (30,000 cycles with 100% retention of C-s). Our results provide an enormous opportunity in designing transition metal oxides decorated semiconducting reduced graphene oxide nanocomposite platforms for various electrochemical applications. (C) 2019 Elsevier Ltd. All rights reserved.